Concurrent Engineering for Uppers Stream Process of Stamping Dies - Senin, Azman; Mohd Nopiah, Zulkifli; Kamal Ariffin Mohd Ihsan, Ahmad; Abdullah, Shahrum; Abd Wahab, Dzuraidah; Zakaria, Ahmad (International Journal of Engineering and Technology, 2018)
The new-product development process is very important to manufacturing companies in all the product being developed. The product being developed must meet all internal company processes, customer requirement and to be delivered at the planned time. The modern approach in new product development is concurrent engineering. This paper reviews the concurrent engineering development and practices in several countries and industry. An investigation on concurrent engineering approach to selected manufacturing companies were conducted and analyzed. Concurrent engineering implementation is moderate due to organizational, tools and communication barriers. Secondly, the use of digital tools such as Electronic Data Management/Computer Aided Engineering/Computer Integrated Manufacturing is low. To ensure the success of concurrent engineering for critical process in new product development such as stamping process, the stamped part accuracy and considerable processing timings are the key factors.Â